Fabrication and superconducting properties of internal Mg diffusion processed MgB2 wires using MgB4 precursors. (15th September 2016) - Xu, Da; Wang, Dongliang; Yao, Chao; Zhang, Xianping; Ma, Yanwei; Oguro, Hidetoshi; Awaji, Satoshi; Watanabe, Kazuo
Abstract: Monofilament MgB2 /Nb/Monel wires were fabricated using three different MgB4 precursors by an internal Mg diffusion (IMD) process. The wire geometry and heat-treatment conditions were optimized in order to improve the critical current density ( J c ) of the MgB2 wire. The influences of the quality of MgB4 powders, such as the particle size and MgO impurity, on the microstructure and superconducting properties of the wires were discussed. Although there were small amounts of voids, unreacted MgB4 particles and MgO impurity existed in the superconducting layers, and the transport layer J c of the wire with the MgB4 precursor reached 3.0 × 10 4 A cm −2 at 4.2 K and 10 T, which was comparable to that of IMD-processed wires fabricated using boron precursors. Both the non-barrier J c and engineering J c of MgB2 wire made using a MgB4 precursor were enhanced due to the improved grain connectivity and the enlarged fill factor.